The extended MRP model for the evaluation and financing of superannuation schemes in a supply chain - Bogataj, David; Vodopivec, Robert; Bogataj, Marija (Technological and Economic Development of Economy, 2014)
The retirement age of industrial workers in national pension schemes is being raised. However, many industrial workers are not able to work until they have reached the increased retirement age. This problem is decreasing social security, increasing workers anxiety regarding the future and influencing the quality and timing of production processes. Disruptions and lower quality items produced in one activity cell of a supply chain can have a ripple effect throughout an entire supply chain. To solve this problem, we should put in place supplementary occupational pension schemes, which would compensate firms for the depreciated ability of their elderly workers to work when they have reached the previous retirement age but have not yet reached the new, higher retirement age. This article is introduces a model that is based on extended MRP Theory. The model can be used as a basis for negotiations between employers and employees to keep production at the same level of quality. The trade-off between higher contributions to supplementary occupational pension schemes and lower added values is considered. Contributions enable the early retirement of industrial workers at one or more workplaces in a supply chain, while lower added value is the result of lower quality and the perturbed timing of items that are produced in one or more activity cells of a supply chain: these issues have a ripple effect throughout an entire supply chain. The net present value approach is used.